2006
DOI: 10.1159/000102051
|View full text |Cite
|
Sign up to set email alerts
|

Association between AMPD1 Gene Polymorphism and Coagulation Factors in Patients with Coronary Heart Disease

Abstract: The aim of this study was to investigate whether the C34T and G468T variations in the adenosine monophosphate deaminase-1 (AMPD1) gene were associated with intima-media thickness of the carotid and brachial artery, endothelial function of the brachial artery, glucose metabolism, haemostatic variables and cardiac hypertrophy in patients (n = 109) with coronary heart disease. The plasminogen activator inhibitor-1 activity and the von Willebrand factor were higher in the CC homozygote group compared to the CT/TT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…In this study, there was no significant association between genotypes and BMI, which is in agreement with previous studies (Rico-Sanz et al, 2003;Kolek et al, 2005;Agewall and Norman, 2006;Collins et al, 2006). In addition, we did not observe a significant association between genotypes and the level of FBS.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, there was no significant association between genotypes and BMI, which is in agreement with previous studies (Rico-Sanz et al, 2003;Kolek et al, 2005;Agewall and Norman, 2006;Collins et al, 2006). In addition, we did not observe a significant association between genotypes and the level of FBS.…”
Section: Discussionsupporting
confidence: 92%
“…In the available studies [10,[12][13][14][15], a similar prevalence of diabetes in T34 allele carriers and CC homozygotes has been described. The only study in which glycaemia was analysed [20] did not find any influence of T allele on fasting glucose, glycaemia during oral glucose tolerance test and serum insulin concentration in post-MI patients. However, in this study, contrary to ours, known diabetes mellitus was the exclusion criterion, and it is not known how many patients with different genotypes were excluded for this reason.…”
Section: Ampd1 and Diabetesmentioning
confidence: 89%
“…Perhaps the presence of patients with HF in these groups was the reason that such a relationship between AMPD1 genotype and morphometric parameters was not observed. In most publications, these parameters were not presented, and in three studies there was no relationship between genotype and BMI in the group of patients with HF [15] and in the groups of post-MI patients, including patients with HF [13,20]. In the cohort from the HERITAGE Family Study, no relationship between C34T polymorphism and weight or BMI was found [21], but this group comprised young (17-40 years) subjects without CAD.…”
Section: Ampd1 and Obesitymentioning
confidence: 96%
“…Of the 13 cluster genes, five belonged to the biological process immune response (p = 0.001), and an additional three had previously been linked to atherosclerosis [17], [18], [19], [20]. These eight genes were phosphatidylinositol glycan class F (PIGF), with pro-angiogenic properties [20]; adenosine monophosphate deaminase 1 (AMPD1), which is involved in insulin clearance and was previously related to cardiovascular morbidities [17], [19]; tumor necrosis factor receptor superfamily member 17 (TNFRSF17), which is essential for B-cell development; Pou domain class 2 associating factor 1 (POU2AF1), which is critical in B-cell-specific B29 promoter expression; proapoptotic caspase adaptor protein (PACAP), a proapoptotic regulator in lymphocytes [18]; X-box binding protein (XBP1), a transcription factor that regulates major histocompatability complex class II genes [21]; major histocompatibility complex class II (HLA-DOB), which is expressed in antigen-presenting cells; and immunoglobulin lambda-like polypeptide 3 (IGLL3). The remaining five genes (DERL3, PIM2, FKBP11, FCRL5, and NM_002694) have not been extensively studied (total PubMed hits  =  155) and have never before been linked to atherosclerotic processes.…”
Section: Resultsmentioning
confidence: 99%